African diasporic cinema aesthetics of reconstruction - Ricci, Daniela 1970- (Michigan State University Press, 2020)
"African Diasporic Cinema: Aesthetics of Reconstruction examines contemporary diasporic African films, explores the aesthetic strategies used by black diasporic filmmakers to express identity reconstruction processes after migration, and highlights their films' continuities with and distances from foundational African films. The analyzed films (by Newton I. Aduaka, Sarah Bouyain, Haile Gerima, Alain Gomis, and Balufu Bakupa-Kanyinda) reflect different personal and artistic paths and various visions between Africa and Europe or the United States"--
Literaturverzeichnis Seite 251-276
"Originally published in French under the title Cinémas des diaspora noires: esthétiques de la reconstruction, Copyright © 2016 L'Harmattan"
Keywords: Blacks in the motion picture industry; Blacks in motion pictures; Motion pictures -- Africa; Film; Africa -- In motion pictures.; Afrika